PENGENALAN PERBANKAN SYARIAH SEBAGAI UPAYA MEWUJUDKAN KETAHANAN MASYARAKAT DI MASA PANDEMI COVID-19 DI KAMPUNG CENGAL, DESA KARACAK, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - M. Reza Nurapriajul; Rully Trihantana; Ria Kusumaningrum (SAHID DEVELOPMENT JOURNAL, 2021)
Abstract The organizer of the community development at the Sahid Islamic Institute of Bogor in 2020 is in the Covid-19 situation that has hit the whole world. The work program carried out by community development is adjusted to the current guidelines. The program is to support the government in breaking the chain of spread of Covid-19, the most important thing is educating the public about the dangers of Covid-19 and running a new life in the new normal era. Especially in Cengal Village, Leuwiliang District, The activity uses the community education method which consists of the stages of initial observation and socialitation, program preparation, program implementation, and evaluation. The results of the evaluation show that the CSP program contributes to increasing public understanding of the Coronavirus, awareness to implement health protocols, productive economic activities, and online learning activities during the enactment of extraordinary conditions. Keywords: Corona Virus; covid-19; pandemic; CSP; public education